2021
DOI: 10.1021/acsaem.1c02834
|View full text |Cite
|
Sign up to set email alerts
|

Triptycene-Based Polymer Embedded in ZnIn2S4 to Construct a Hierarchical Heterostructure for Efficient Photocatalytic Hydrogen Evolution

Abstract: Development of promising photocatalysts with a synergistic effect for hydrogen generation holds paramount significance for solving the global energy problem. Herein, we rationally design a hierarchical heterostructure in which a triptycene covalent polymer (TCP) is grown in situ on ZnIn 2 S 4 through a Suzuki coupling reaction. Assorted experimental results demonstrate that amorphous TCP with a high BET surface area (903 m 2 g −1 ) is embedded on 2D ZnIn 2 S 4 nanoflakes by a self-assembly process, thus indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…The first one was the value of the optimized H 2 evolution rate, and the second one was the enhancement multiple of the rate after building the heterojunction. Herein, the production rate of 10%M/Z (3730.5 μmol/g/h) outperformed those of the reported ZnIn 2 S 4 @In(OH) 3 (101 μmol/g/h), 41 2 wt % WN@ C/ZnIn 2 S 4 (196.0 μmol/g/h), 57 ZnIn 2 S 4 /TCP (1432.8 μmol/ g/h), 58 O-doped ZnIn 2 S 4 (2120 μmol/g/h), 59 ZnIn 2 S 4 @NH 2 -MIL(Ti) (2204.2 μmol/g/h), 37 and NiS/ZnIn 2 S 4 (3333.3 μmol/g/h) 1 and was even higher than that of 3 wt % Pt loading-ZnIn 2 S 4 @Ti 3 C 2 T x (3475 μmol/g/h). 13 Although the rate was lower than those of ZnIn 2 S 4 @PCN-224 (5680 μmol/ g/h), 60 NiCo 2 S 4 /ZnIn 2 S 4 (6834.6 μmol/g/h), 25 and S v -ZIS/ MoSe 2 (63,210 μmol/g/h), 61 the activity enhancement multiple after MoO 2 modification in this work was notably higher than these photocatalysts.…”
Section: Photocatalytic H 2 -Evolvingmentioning
confidence: 82%
“…The first one was the value of the optimized H 2 evolution rate, and the second one was the enhancement multiple of the rate after building the heterojunction. Herein, the production rate of 10%M/Z (3730.5 μmol/g/h) outperformed those of the reported ZnIn 2 S 4 @In(OH) 3 (101 μmol/g/h), 41 2 wt % WN@ C/ZnIn 2 S 4 (196.0 μmol/g/h), 57 ZnIn 2 S 4 /TCP (1432.8 μmol/ g/h), 58 O-doped ZnIn 2 S 4 (2120 μmol/g/h), 59 ZnIn 2 S 4 @NH 2 -MIL(Ti) (2204.2 μmol/g/h), 37 and NiS/ZnIn 2 S 4 (3333.3 μmol/g/h) 1 and was even higher than that of 3 wt % Pt loading-ZnIn 2 S 4 @Ti 3 C 2 T x (3475 μmol/g/h). 13 Although the rate was lower than those of ZnIn 2 S 4 @PCN-224 (5680 μmol/ g/h), 60 NiCo 2 S 4 /ZnIn 2 S 4 (6834.6 μmol/g/h), 25 and S v -ZIS/ MoSe 2 (63,210 μmol/g/h), 61 the activity enhancement multiple after MoO 2 modification in this work was notably higher than these photocatalysts.…”
Section: Photocatalytic H 2 -Evolvingmentioning
confidence: 82%
“…1a, the PXRD of C 3 N 4 and C 3 N 4 (180) show two diffraction peaks at 13.2° and 27.5° corresponding to (100) and (002) planes (JCPDS 87-1526), which can be assigned to the reduplicative tris-heterocycle packing and the interlayer stacking of aromatic segments 28 Besides, the peak intensity of C 3 N 4 (180) decreases compared with C 3 N 4 , implying thinner nanosheet structure. As for ZnIn 2 S 4 , the PXRD diffraction peaks are at 21.5°, 27.6°, 30.4°, 39.8°, 47.1°, 52.3° and 55.5°, which are ascribed to the (006), (102), (104), (108), (110), (116) and (202) crystal facets with hexagonal crystal ZnIn 2 S 4 (JCPDS 65-2023) 29 Compared with C 3 N 4 , C 3 N 4 (180) and ZnIn 2 S 4 , the PXRD patterns of XZnIn 2 S 4 /C 3 N 4 (180) and 40ZnIn 2 S 4 /C 3 N 4 nanocomposites are similar to that of ZnIn 2 S 4 , but PXRD diffraction peaks of C 3 N 4 were not apparent. The main reason is the coincidence of the diffraction peaks of 27.5°.…”
Section: Resultsmentioning
confidence: 96%
“…Since from a few decades, researchers have proposed many different strategies or routes to overcome these restrictions, including co-catalyst loading, crystal facet engineering, construction of different surface morphology with porous structure, band gap engineering, and construction of homo or hetero-junctions (binary, ternary), etc. [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] To avoid the recombination of charge carriers, noble metal nanoparticles have been widely used as efficient cocatalysts decorated on semiconductor photocatalysts. Many researchers have reported that noble metal NPs, such as Au, Pt, Ag, Rh, Ni-Pt, Pd, Cu-Pd, and Au-Pd have been reported resulting in enhanced overall photocatalytic activity by enhancing the electron-hole charge separation.…”
Section: Introductionmentioning
confidence: 99%